The Fauna of Springtails (Collembola) in Lviv - Shrubovych, J. (Вестник зоологии, 2002)
119 species of Collembola have been recorded in various ecosystems of Lviv, differing by degree of the urban pressure. Successful coexistence of great number of springtail species with different ecological preferences (forest, meadow, meadow-steppe, eurytopic, compost, ruderal, synanthropic, troglophilous forms) is the most characteristic peculiarity of faunal communities in urban conditions. 119 видов ногохвосток зарегистрированы в различающихся степенью урбопресса экосистемах города Львова. Успешное сосуществование большого числа видов коллембол с разными экологическими преферендумами (лесных, луговых, лугостепных, эвритопных, компостных, рудеральных, синантропных, троглофильных форм) является наиболее характерной особенностью фаунистических комплексов в условиях урбосреды.